PEMANFAATKAN AMPAS KELAPA DAN AMPAS KELAPA FERMENTASI DALAM RANSUM TERHADAP EFESIENSI RANSUM DAN INCOME OVER FEED COST AYAM PEDAGING - Moh. Yamin (Universitas Tadulako, 2008)
The experiment to study the effect of coconut kernel (RCK) and fermented coconut kernel wastes (FCKS) on feed efficiency and income over feed cost of broiler was conducted from September to October 2006. The experiment used 100 DOC (Arbor Acres Strain) broilers. A Completely Randomized Design was applied with 5 treatments with 4 replicates. The treatments were R0 = 0% RCK and RCKF; R1 = 6% RCK; R2 = 12% RCK; R3 = 6% RCKF and R4 = 12% RCKF. The results of the experiment showed that the treatment effects on the feed efficiency of broiler were highly significant (P<0.01). The treatments R3 and R4 were more efficient than R1 and R2. The R4 treatment produced the best income over feed Cost (± Rp 6897.88), whereas the R2 treatment shown the lowest one (± Rp 4396.65). In order to apply the waste of coconut kernel, it is recomended that it should be fermented at first to improve its quality and to increase the income over feed cost of broiler.